Enzyme‐ and transporter‐mediated beverage–drug interactions: An update on fruit juices and green tea. (30th July 2015) - An, Guohua; Mukker, Jatinder Kaur; Derendorf, Hartmut; Frye, Reginald F.
Abstract: Beverage–drug interactions have remained an active area of research and have been the subject of extensive investigations in the past 2 decades. The known mechanisms of clinically relevant beverage–drug interactions include modulation of the activity of cytochrome P450 (CYP) 3A and organic anion‐transporting polypeptide (OATP). For CYP3A‐mediated beverage–drug interaction, the in vivo CYP3A inhibitory effect is limited to grapefruit juice (GFJ), which increases the bioavailability of several orally administered drugs that undergo extensive first‐pass metabolism via enteric CYP3A. In contrast, clinically significant OATP‐mediated beverage–drug interactions have been observed with not only GFJ but also orange juice, apple juice, and, most recently, green tea. Fruit juices and green tea are all a mixture of a large number of constituents. The investigation of specific constituent(s) responsible for the enzyme and/or transporter inhibition remains an active area of research, and many new findings have been obtained on this subject in the past several years. This review highlights the multiple mechanisms through which beverages can alter drug disposition and provides an update on the new findings of beverage–drug interactions, with a focus on fruit juices and green tea.